Photon-upconverting chiral liquid crystal: significantly amplified upconverted circularly polarized luminescence. Issue 1 (11th October 2018) - Yang, Xuefeng; Han, Jianlei; Wang, Yafei; Duan, Pengfei
Abstract : By blending a chiral acceptor and a sensitizer into a nematic liquid crystal, a chiral nematic liquid crystal showing amplified upconverted circularly polarized luminescence could be obtained. Abstract : In this work, we demonstrate a room-temperature chiral liquid crystal which shows remarkable photon upconverted circularly polarized luminescence (UC-CPL). Circularly polarized luminescent materials with higher dissymmetry factor ( g lum ) underpin the basis for future applications. Since most chiral organic molecules have only a small g lum, it is vital to explore a new pathway to amplify the g lum of organic compounds. Here, by dispersing a chiral emitter and a triplet donor into a room-temperature nematic liquid crystal, highly efficient triplet–triplet annihilation-based photon upconversion (TTA-UC) and UC-CPL were observed in the induced chiral nematic liquid crystal (N*LC). Moreover, this system could simultaneously amplify the promoted circularly polarized luminescence (CPL) and the upconverted circularly polarized luminescence. The dissymmetry factors g lum of CPL and UC-CPL have been amplified by three orders of magnitude and one order of magnitude, respectively.